Ischemic stroke and shift work - Hermansson, Jonas; Gillander Gådin, Katja; Karlsson, Berndt; Lindahl, Bernt; Stegmayr, Birgitta; Knutsson, Anders (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'This study analyzed the potential association between shift work and ischemic stroke. ' ' METHODS ': 'The analysis was carried out using a nested case–control study consisting of 138 shift workers and 469 day workers from the register of the Northern Sweden Monitoring of Trends and Determinants in Cardiovascular Diseases (MONICA) study and the Västerbotten Intervention Programme. Logistic regression analysis was used to analyze the risk estimate for day workers in a comparison with shift workers and the risk of ischemic stroke. ' ' RESULTS ': 'The crude odds ratio for shift workers’ risk of experiencing an ischemic stroke was 1.0 (95% confidence interval 0.6–1.8) for both the men and the women. The risk estimates were consistent despite the introduction of several recognized risk factors for ischemic stroke in the logistic regression models. ' ' CONCLUSIONS ': 'In the present study, none of the findings indicated a higher risk of shift workers undergoing an ischemic stroke than day workers.
Keywords: cardiovascular disease; case–control study; epidemiology; ischemic stroke; risk factor; shift work